Ein Länderfinanzausgleich ohne Berlin - Gewinner und Verlierer - Martina Kuntze (Wirtschaftsdienst, 2013)
Berlin hat als Empfängerland des Länderfinanzausgleichs regelmäßig mehr als ein Drittel der Ausgleichsmasse erhalten. Am stärksten belastet ist Bayern, das gemeinsam mit Hessen gegen die Struktur des Länderfinanzausgleichs klagen möchte. Die Autorin schlägt vor, Berlin bereits bei der Umsatzsteuerverteilung zu begünstigen. Allerdings werden bei dieser Lösung vor allem Bayern und Hessen verlieren. – – The author simulates the federal financial equalisation system in Germany without Berlin with respect to the adjustment year 2011. The model assumes that the capital city is compensated by the distribution of value added tax (VAT). Hence winners as well as losers can be identified at both stages of adjustment within the federal financial equalisation system. The result clarifies the position of Hesse and Bavaria, which intend to take legal action against the German federal financial equalisation system. In particular these two German states should not push for the exclusion of Berlin in this context. Otherwise the scenario would lead to considerable losses for both states.
Keywords: H72; H73; H77; 330; Berlin; Länderfinanzen; Horizontaler Finanzausgleich; Umsatzsteuer; Deutschland